The role of Nrf2 and PPARgamma in the improvement of oxidative stress in hypertension and cardiovascular diseases - Dovinová, Ima; Kvandová, Miroslava; Bališ, Peter; Grešová, Linda; Majzúnová, Miroslava; Horáková, Ľubica; Chan, J. Y. H; Barančík, Miroslav (Physiological research, 2020)
Reactive oxygen species are an important element of redox regulation in cells and tissues. During physiological processes, molecules undergo chemical changes caused by reduction and oxidation reactions. Free radicals are involved in interactions with other molecules, leading to oxidative stress. Oxidative stress works two ways depending on the levels of oxidizing agents and products. Excessive action of oxidizing agents damages biomolecules, while a moderate physiological level of oxidative stress (oxidative eustress) is necessary to control life processes through redox signaling required for normal cellular operation. High levels of reactive oxygen species (ROS) mediate pathological changes. Oxidative stress helps to regulate cellular phenotypes in physiological and pathological conditions. Nrf2 (nuclear factor erythroid 2-related factor 2, NFE2L2) transcription factor functions as a target nuclear receptor against oxidative stress and is a key factor in redox regulation in hypertension and cardiovascular disease. Nrf2 mediates transcriptional regulation of a variety of target genes. The Keap1-Nrf2-ARE system regulates many detoxification and antioxidant enzymes in cells after the exposure to reactive oxygen species and electrophiles. Activation of Nrf2/ARE signaling is differentially regulated during acute and chronic stress. Keap1 normally maintains Nrf2 in the cytosol and stimulates its degradation through ubiquitination. During acute oxidative stress, oxidized molecules modify the interaction of Nrf2 and Keap1, when Nrf2 is released from the cytoplasm into the nucleus where it binds to the antioxidant response element (ARE). This triggers the expression of antioxidant and detoxification genes. The consequence of long-term chronic oxidative stress is activation of glycogen synthase kinase 3beta (GSK-3beta) inhibiting Nrf2 activity and function. PPARgamma (peroxisome proliferator-activated receptor gamma) is a nuclear receptor playing an important role in the management of cardiovascular diseases, hypertension and metabolic syndrome. PPARgamma targeting of genes with peroxisome proliferator response element (PPRE) has led to the identification of several genes involved in lipid metabolism or oxidative stress. PPARgamma stimulation is triggered by endogenous and exogenous ligands - agonists and it is involved in the activation of several cellular signaling pathways involved in oxidative stress response, such as the PI3K/Akt/NOS pathway. Nrf2 and PPARgamma are linked together with their several activators and Nrf2/ARE and PPARgamma/PPRE pathways can control several types of diseases.
Keywords: Animals; hypertenze; NF-E2-Related Factor 2; oxidační stres; PPAR gama; Oxidative Stress; lidé; Reactive Oxygen Species; faktor 2 související s NF-E2; signální transdukce; Signal Transduction; krevní tlak; Hypertension; Cardiovascular Diseases; KEAP-1; Kelch-Like ECH-Associated Protein 1; reaktivní formy kyslíku; kardiovaskulární nemoci; antioxidační responzivní elementy; zvířata; Blood Pressure; Antioxidant Response Elements; PPAR gamma; Humans